THE CREDIBILITY OF CONSUMER REVIEWS ON THREE E-COMMERCE IN INDONESIA: MIXED METHOD APPROACH - Wahpiyudin, Cep Abdul Baasith; Mahanani, Raditya Kasih; Rahayu, Ismie Leona; Simanjuntak, Megawati; Sumarwan, Ujang; Yuliati, Lilik Noor; Djamaludin, Moh. Djemdjem; Johan, Irni Rahmayani; Muflikhati, Istiqlaliyah (Jurnal Ilmu Keluarga dan Konsumen, 2022)
Online stores with more than 3000 reviews have made it difficult for consumers to find reviews that can be used as the main source of information to decide on a purchase. This research aims to investigate the credibility of reviews that consumers can be trusted. This research used mixed methods (quantitative and qualitative) through sequential explanation. In this quantitative study, 300 respondents were collected using a voluntary sampling technique, and 900 reviews from three e-commerce sites in Indonesia were selected purposely. The qualitative approach used in-depth interviews with three consumers and a selected seller using a purposive sampling technique. The data was processed by multiple linear regression and descriptive using SPSS 25.0 and Nvivo 12. Research results confirmed that the motivation to read reviews and consumer attitudes toward reviews significantly affect online purchasing decisions, but a third of consumers still rarely provide reviews. Furthermore, based on source credibility, E-WOM quality, and recommendation rating, in the three e-commerce sites, almost half of the reviews studied were hard to be trusted. Based on these findings, this research summarizes the policy implications for consumers and governments and suggests future research.